Investigating the addition of SiO2–CaO–ZnO–Na2O–TiO2 bioactive glass to hydroxyapatite: Characterization, mechanical properties and bioactivity. (November 2015) - Yatongchai, Chokchai; Placek, Lana M; Curran, Declan J; Towler, Mark R; Wren, Anthony W
Hydroxyapatite (Ca10 (PO4 )6 (OH)2 ) is widely investigated as an implantable material for hard tissue restoration due to its osteoconductive properties. However, hydroxyapatite in bulk form is limited as its mechanical properties are insufficient for load-bearing orthopedic applications. Attempts have been made to improve the mechanical properties of hydroxyapatite, by incorporating ceramic fillers, but the resultant composite materials require high sintering temperatures to facilitate densification, leading to the decomposition of hydroxyapatite into tricalcium phosphate, tetra-calcium phosphate and CaO phases. One method of improving the properties of hydroxyapatite is to incorporate bioactive glass particles as a second phase. These typically have lower softening points which could possibly facilitate sintering at lower temperatures. In this work, a bioactive glass (SiO2 –CaO–ZnO–Na2 O–TiO2 ) is incorporated (10, 20 and 30 wt%) into hydroxyapatite as a reinforcing phase. X-ray diffraction confirmed that no additional phases (other than hydroxyapatite) were formed at a sintering temperature of 560 ℃ with up to 30 wt% glass addition. The addition of the glass phase increased the % crystallinity and the relative density of the composites. The biaxial flexural strength increased to 36 MPa with glass addition, and there was no significant change in hardness as a function of maturation. The pH of the incubation media increased to pH 10 or 11 through glass addition, and ion release profiles determined that Si, Na and P were released from the composites. Calcium phosphate precipitation was encouraged in simulated body fluid with the incorporation of the bioactive glass phase, and cell culture testing in MC-3T3 osteoblasts determined that the composite materials did not significantly reduce cell viability.